English Adjectives Used by Non-natives in ICNALE Spoken Dialogues - Faiz, Adinda (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2024)
The purpose of this study is to examine English adjectives found in spoken language corpus of English learners in Asia. This study employed theories of adjectives from language typology perspective by Dixon (2010) and Frawley (1992). Descriptive-qualitative approach was applied, using ICNALE Spoken Dialogues as the data source. This study utilized the corpus analysis tools AntConc. The results identified the top 20 adjectives in the corpus, with Value, Human Propensity, and Difficulty each representing 20% of the findings. This study has implications for the significance of foreign language learning. Teachers can use adjectives from these categories to teach students, as they are basic vocabularies for English learners. Students are also expected to gain a better understanding of the functional aspect of adjectives, which could improve their language performance. The interest of this study lies in the high frequency of occurrence in the corpus. However, some limitations should also be considered.